Annotinolide F and lycoannotines A–I, further Lycopodium alkaloids from Lycopodium annotinum. (November 2017) - Tang, Yu; Xiong, Juan; Zou, Yike; Wang, Wei; Huang, Chao; Zhang, Hai-Yan; Hu, Jin-Feng
Abstract: Seven lycopodine-type (annotinolide F and lycoannotines A–F), two lycodine-type (lycoannotines G and H), and one fawcettimine-type (lycoannotine I) previously undescribed naturally occurring Lycopodium alkaloids together with thirteen known ones were isolated from the whole plant of Lycopodium annotinum . Their structures and absolute configurations were determined by extensive spectroscopic methods, single-crystal X-ray diffraction, chemical transformation, and electronic circular dichroism (ECD) calculations. Among the isolates, annotinolide F, lycoannotines A and B are unusual 7, 8- seco -lycopodane derivatives, and annotinolide F even further possesses a rare 8, 5-lactone framework through a lactonization after the C-7/C-8 bond cleavage. Lycoannotine C is an uncommon 8, 15- seco lycopodine-type alkaloid, whereas lycoannotine I represents the first example of a naturally occurring C-9/ N bond cleavage product of fawcettimine-type alkaloid. Among them, only lycoannotine I was found to show considerable anti-butyrylcholinesterase (anti-BuChE) activity. Graphical abstract: Ten previously undescribed Lycopodium alkaloids together with thirteen known ones were isolated from the whole plant of Lycopodium annotinum . Among them, lycoannotine I showed anti-BuChE activity. Highlights: Ten hitherto unknown Lycopodium alkaloids were isolated from Lycopodium annotinum. Their absolute configurations were determined by extensive methods. Annotinolide F has an unusual 7, 8- seco -lycopodane-derived 8, 5-lactone skeleton. Lycoannotine C is an uncommon 8, 15- seco lycopodine-type alkaloid. Lycoannotine I is the first fawcettimine alkaloid with a cleavage of the C-9/ N bond.